Tuning the oxygen reduction reactivity of interconnected porous carbon by incorporation of phosphorus and activity enhancement through blending with 2D metal dichalcogenides materials. (1st March 2018) - Mutyala, S.; Rajaram, R.; Karuppasamy, D.; Suresh, C.; Mathiyarasu, J.
Abstract: Design and construction of strong oxygen reduction reaction (ORR) electrocatalysts with high activity and durability are the main concerns in proton exchange membrane fuel cells (PEMFCs). In this study, a unique interconnected porous carbon (ICPC) and phosphorus doped ICPC (P-ICPC) were synthesized and utilized as a support matrix for ORR in alkaline medium. The activity of P-ICPC further enhanced by compositing with 2D metal dichalcogenide MoS2 materials through facile hydrothermal method. The structural characterization indicated that the addition of phosphorus created more defective site in the carbon structure. The MoS2 /P-ICPC catalyst exhibited enhanced ORR activity, and its performance is close to commercial Pt/C catalyst with regards to current density and onset potential. The synthesized MoS2 /P-ICPC catalyst shows better stability regarding activity even after the 2000 cycles of acceleration test. The electron transfer number (n) obtained for MoS2 /P-ICPC is ∼3.8, indicating that the oxygen reduction reaction proceeds via 4e − pathway with the similar kinetics of commercial Pt/C. The current results revealed that the synthesized MoS2 /P-ICPC material might be a better catalyst for oxygen reduction reaction. Graphical abstract: Highlights: Utilization of interconnected porous carbon for oxygen reduction reaction. O2 reduction efficiency of carbon enhances with phosphorous incorporation. Defect surface originating through phosphorous addition. MoS2 /P-ICPC composite shows better ORR activity. Activity closer to commercial platinum catalyst with improved methanol tolerance.